Bringing theory to life: integrating case-based learning in applied physiology for undergraduate physiotherapy education - Rehab E. Abo Elgheit; Nagwa Nashat (BMC Medical Education)
Abstract Background Case-based learning (CBL) is considered an effective teaching approach that provides medical students with a learning environment simulating future actual practice. So we aimed to implement CBL, as an additional component to traditional teaching methods (TTMs) in applied physiology for undergraduate physiotherapy students (UPS) and to evaluate its impact on students’ perception and academic performance compared to TTMs alone. Methods CBL was implemented during the teaching of applied physiology throughout the neuroscience course in the 4th semester for UPS. Nine cases related to the topics taught were selected. The academic achievement was evaluated through the students’ grades, and the students’ perception and facilitators’ feedback were explored through a structured, web-based perception questionnaire. Results Of the 244 UPS students, 238 completed the survey following the CBL approach. A total of 97.5% reported a higher perception of the combined CBL with TTMs compared to the traditional approach, with a median overall perception score of 99.0. 93.3% of the enrolled students ensured that combined CBL with TTMs was better in all features in applied physiology education. Integrating CBL with TTMs was associated with improved academic performance. While the maximum grade remained consistent at 10 for both traditional physiology labs and combined CBL with TTMs, the minimum grade improved significantly from 2.0 in traditional lab teaching to 7.5 in combined CBL and TTMs. Median grades also increased from 8.5 to 10.0 when CBL was combined with TTMs, with better performance observed at both the 25th and 75th percentiles under the hybrid CBL and TTMs approach (10.0 vs. 7.0 and 10.0 vs. 9.5, respectively). Conclusion Incorporating CBL alongside TTMs provided a more engaging learning experience, with increased students’ perception, and promoted their academic achievement. An enhanced teaching framework with the integration of CBL can be broadly implemented as a more interactive teaching tool not only in applied physiology but also in other health sciences to overcome the limitations of the TTMs and ensure better outcomes.